Tinjauan Hukum Ketenagakerjaan dalam Mengatasi Pengangguran Terdidik Pada Era Revolusi Industri 4.0 - Susianto, Agus (Fakultas Hukum Universitas Borneo Tarakan, 2018)
This article aims to find the solution to educated unemployment in Industrial Revolution 4.0 era. The issue lies on imparity of the size of the labor force with the inadequacy of job vacancy which adds more problems to employment sector. The data from Badan Pusat Statistik show that unemployment is more prevalent among high school and university graduates than in diploma graduates. On the other hand, many entrepreneurs admit they have difficulties in finding prospective workers who are able to meet the desirable criteria. The existence of regulations that control foreign workers can be accommodated in order to overcome the need for more labor force. However, these regulations have to be examined further, since its existence should not under any circumstances reduce the opportunity of Indonesian labor forces to work in their own country. Solutions are required to overcome these problems. Each party can help reduce the high unemployment rate in Industrial Revolution 4.0. The government plays a crucial role in lessening the rate of educated unemployment. They are able to evaluate labor laws to protect workers and respond to the Industrial Revolution 4.0 era. Moreover, the government is encouraged to review the existing curriculum in each education level in order to assist graduates in developing soft skills and hard skills required in the Industrial Revolution 4.0 era. Each educational unit has to focus specifically to prepare their prospective graduates by implementing more practical learning. Furthermore, graduates should think more innovatively in creating new job opportunities in Industrial Revolution 4.0 era.